2004
DOI: 10.1161/01.cir.0000118467.53182.d1
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Right Ventricular Activation Contributes to Brugada Syndrome

Abstract: Background-Although Brugada syndrome revolves around reduced net depolarizing force, the electrophysiological mechanisms of its defining features (right precordial ST-segment elevation and ventricular tachyarrhythmias) remain unresolved. Two proposed mechanisms are (1) right ventricular (RV) conduction delay and (2) selective and significant RV subepicardial action potential shortening. Both mechanisms must cause disparate contractile changes: delay in RV contraction and reduction of contractile force, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 34 publications
9
123
2
1
Order By: Relevance
“…21 Although there is convincing experimental evidence to support this hypothesis, an additional involvement of altered conduction in the pathophysiological sequence leading to this complex disease cannot be excluded. 22,23 Indeed, the frontier between the Brugada syndrome and progressive conduction diseases remains unclear, because in the same family, the same mutation can induce both diseases. 24 Whether the pathophysiology of the Brugada syndrome also involves myocardial fibrosis (either diffuse or localized in the upper right ventricle) remains to be established, particularly for the fraction of Brugada patients carrying a SCN5A mutation leading to haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although there is convincing experimental evidence to support this hypothesis, an additional involvement of altered conduction in the pathophysiological sequence leading to this complex disease cannot be excluded. 22,23 Indeed, the frontier between the Brugada syndrome and progressive conduction diseases remains unclear, because in the same family, the same mutation can induce both diseases. 24 Whether the pathophysiology of the Brugada syndrome also involves myocardial fibrosis (either diffuse or localized in the upper right ventricle) remains to be established, particularly for the fraction of Brugada patients carrying a SCN5A mutation leading to haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…8,[17][18][19] Depolarization abnormality is reflected in prolonged HV intervals, abnormal late potential and abnormal delayed potential in the epicardial region of the right ventricular outflow tract. 8,16,[20][21][22] A widening of the S wave in the right precordial leads, reflecting an underlying right ventricular conduction delay, was frequently observed in symptomatic patients and might be an important indicator of increased risk. 23 However, rate-dependent changes in the conduction abnormality have not been fully elucidated.…”
Section: Rate-dependent Changes In S Wave and Qrs Durationmentioning
confidence: 99%
“…A recent report showed that such fractionated QRS may have some relationship with their arrhythmic events in patients with type 1 ECG (Morita et al 2008). Other study also showed that right ventricular conduction is delayed in patients with Brugada syndrome (Tukkie et al 2004). Depolarization abnormalities noted in these studies may contribute to the development of late potentials in patients with Brugada syndrome.…”
Section: Late Potentials By Sa-ecgmentioning
confidence: 83%